Effect of Effluent Recirculation on Biogas Production Using Two-Stage Anaerobic Digestion of Citrus Waste - Lukitawesa (Molecules, 2018)
Citrus waste is a promising potential feedstock for anaerobic digestion, yet the presence of inhibitors such as d-limonene is known to limit the process. Effluent recirculation has been proven to increase methane yield in a semi-continuous process for recalcitrant material, but it has never been applied to toxic materials. This study was aimed to investigate the effect of recirculation on biogas production from citrus waste as toxic feedstock in two-stage anaerobic digestion. The first digestion was carried out in a stirred tank reactor (STR). The effluent from the first-stage was filtered using a rotary drum filter to separate the solid and the liquid phase. The solid phase, rich in hydrophobic D-limonene, was discarded, and the liquid phase containing less D-limonene was fed into the second digester in an up-flow anaerobic sludge bed (UASB) reactor. A high organic loading rate (OLR 5 g VS/(L·day)) of citrus waste was fed into the first-stage reactor every day. The effluent of the first-stage was then fed into the second-stage reactor. This experiment was run for 120 days. A reactor configuration without recirculation was used as control. The result shows that the reactor with effluent recirculation produced a higher methane yield (160–203 NmL/g·VS) compared to that without recirculation (66–113 NmL/g·VS). More stable performance was also observed in the reactor with recirculation as shown by the pH of 5–6, while without recirculation the pH dropped to the range of 3.7–4.7. The VS reduction for the reactor with recirculation was 33–35% higher than that of the control without recirculation. Recirculation might affect the hydrolysis-acidogenesis process by regulating pH in the first-stage and removing most of the D-limonene content from the substrate through filtration.